A Good Time to Plant Seed - Kim, Dong-Won (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
In this piece, percussionist Dong-Won Kim (Silkroad Ensemble) argues for the pandemic as an opportunity to rethink aspects of society, including the arts. This is the time for humanity to “engage in a collective improvisation,” he writes, and work towards “lasting change for ourselves and for future generations.”